Determination of methylparaben by differential pulse voltammetry using a glassy carbon electrode modified with polypyrrole - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2015)
A new modified glassy carbon electrode (GCE) based on a synthesized polypyrrole (PPy) was developed for the determination of methylparaben by differential pulse voltammetry (DPV). PPy was covalently immobilized on GCE surface using tetraethyl ammonium perchlorate (TEAP) and acetonitrile (ACN). Methylparaben was oxidized by differential pulse voltammetry and a peak was observed at 1.20 V. The calibration curve obtained with differential pulse voltammetry was linear in the concentration range from 0.01 to 5 mM methylparaben with a limit of detection of 8 x10(-3) mM and RSD of 0.11%. The improved method was applied to the determination of methylparaben in cream samples using the differential pulse voltammetry method.
Keywords: differential pulse voltammetry; modified glassy carbon electrode; methylparaben; polypyrrole; PERFORMANCE LIQUID-CHROMATOGRAPHY; DOPED DIAMOND ELECTRODE; ELECTROCHEMICAL DETECTION; CONDUCTING POLYMER; METHYL PARABEN; SENSOR; COSMETICS; TYROSINE